Eosinophils, but Not Type 2 Innate Lymphoid Cells, Are the Predominant Source of Interleukin 4 during the Innate Phase of Leishmania major Infection - Sasse, Carolin; Barinberg, David; Obermeyer, Stephanie; Debus, Andrea; Schleicher, Ulrike; Bogdan, Christian (Pathogens, 2022)
Interleukin (IL)-4 plays a central role in the initiation of a type 2 T helper cell (Th2) response, which leads to non-healing and progressive infections with the protozoan parasite Leishmania (L.) major. Here, we tested the hypothesis that type 2 innate lymphoid cells (ILC2), which promote the development of Th2 cells, form an important source of IL-4 early after intradermal or subcutaneous L. major infection. Lineage-marker negative CD90.2(+)CD127(+)PD1(-) ILC2 were readily detectable in the ear or foot skin, but hardly in the draining lymph nodes of both naive and L. major-infected self-healing C57BL/6 and non-healing BALB/c mice and made up approximately 20% to 30% of all CD45(+)SiglecF(-) cells. Dermal ILC2 of C57BL/6 mice expressed the inducible T cell-costimulator (ICOS, CD278), whereas BALB/C ILC2 were positive for the stem cell antigen (Sca)-1. Within the first 5 days of infection, the absolute numbers of ILC2 did not significantly change in the dermis, which is in line with the unaltered expression of cytokines activating (IL-18, IL-25, IL-33, TSLP) or inhibiting ILC2 (IL-27, IFN-gamma). At day 5 to 6 post infection, we observed an upregulation of IL-4, but not of IL-5, IL-10 or IL-13 mRNA. Using IL-4-reporter (4get) mice, we found that the production of IL-4 by C57BL/6 or BALB/c mice was largely restricted to CD45(+)FSiglecF(+) cells of high granularity, i.e., eosinophils. From these data, we conclude that eosinophils, but not ILC2, are a major innate source of IL-4 at the skin site of L. major infection.
CRIS-Team WoS Importer:2022-09-09